Microsatellite Instability and Loss of Heterozygosity in CCND1 Microsatellite loci at Chr.11q13 in OSCC Patients with Therapeutic Validation - Seema Gupta; Shally Batham; Biswajit Maity (The Saint's International Dental Journal)
Background: Numerous prognostic biological markers linked to survival have been identified over the years; however, only few have undergone rigorous evaluation for their diagnostic accuracy. Molecular laboratory techniques like microarrays, microsatellites, and single-nucleotide polymorphisms (SNPs) have created new opportunities for diagnosing diseases, identifying chromosomal aberrations, and detecting point mutations for medical verification. The deviation of CCND1-cyclinD1 loci on chromosome 11Q13 is identified as a genetic marker for esophageal, breast, colon, rectal, and ovarian cancers. Materials and Methods: A total of 18 microsatellite markers located on 11q13 were analyzed in 150 patients with oral squamous cell carcinoma (OSCC), who were treated with cisplatin and capecitabine. The study aimed at early detection, clinical validation, and the establishment of genetic markers. We collected 150 primary tumor tissues and corresponding blood samples from patients visiting King George’s Medical University in Lucknow between 2010 and 2016. Tissue samples were obtained either at the time of investigational biopsy or during the surgical resection of the lesions. Results: The overall incidence of loss of heterozygosity (LOH)/microsatellite instability (MSI) was 60%±20.84, with the frequency of LOH and MSI of individual markers ranging from 9% to 95%. LOH/MSI was relatively more frequently detected at five loci, namely, FGF4 (65.33%/11%), FGF3 (77.33%/13.23%), INT2 (64%/12.8%), CCND1 (88%/ 15.13%), and D11S2179 (61.33%/12.66%). Conclusion: This report presents the initial findings suggesting a potential association between allelic loss at the CCND1 locus on chromosome 11q13 and the recurrence of OSCC in Indian patients treated with cisplatin and capecitabine. Further research in this area may provide valuable insights.